2018
DOI: 10.1177/0278364918804660
|View full text |Cite
|
Sign up to set email alerts
|

A convex-programming-based guidance algorithm to capture a tumbling object on orbit using a spacecraft equipped with a robotic manipulator

Abstract: An algorithm to guide the capture of a tumbling resident space object by a spacecraft equipped with a robotic manipulator is presented. A solution to the guidance problem is found by solving a collection of convex programming problems. As convex programming offers deterministic convergence properties, this algorithm is suitable for onboard implementation and real-time use. A set of hardware-in-the-loop experiments substantiates this claim. To cast the guidance problem as a collection of convex programming prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 69 publications
(94 reference statements)
0
39
0
Order By: Relevance
“…In order to cast both sub-maneuver optimization problems as convex programming problems, they are converted to fixedfinal-time problems. As discussed by Virgili-Llop et al (2019), and later shown in section 5, longer final times, t f , reduce, in broad terms, the cost of the maneuver. The user is then prompted to select the longest possible maneuver duration, only limited by the available computing power, or by other factors as communication, or illumination windows.…”
Section: Selecting the Initial And Final Timementioning
confidence: 76%
See 2 more Smart Citations
“…In order to cast both sub-maneuver optimization problems as convex programming problems, they are converted to fixedfinal-time problems. As discussed by Virgili-Llop et al (2019), and later shown in section 5, longer final times, t f , reduce, in broad terms, the cost of the maneuver. The user is then prompted to select the longest possible maneuver duration, only limited by the available computing power, or by other factors as communication, or illumination windows.…”
Section: Selecting the Initial And Final Timementioning
confidence: 76%
“…A seed to the sequential convex programming procedure is obtained during the first iteration, k = 1, by removing the keep-out zone constraint in Equation (52) from the convex programming problem. The sequential convex programming procedure of the systemwide translation enjoys guaranteed convergence to a locally optimal point-meeting the Karush-Kuhn-Tucker conditions (Boyd and Vandenberghe, 2004)-even if the RSO's shape, S RSO , is non-convex (Virgili-Llop et al, 2019). To obtain these convergence properties replace, during the second iteration k = 2, the RSO shape, S RSO , by its convex hull.…”
Section: Step 1: Optimization Of the System-wide Translationmentioning
confidence: 99%
See 1 more Smart Citation
“…robot tracking control. It is often used for grasping tumbling satellites [6]- [9], and face tracking [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the aerospace industry has placed increasingly stringent requirements on the performance of space manipulators [1], [2]. If the arms are required to be light in weight, large in end load, and capable of capture maneuvers [3], its own elastic deformation must be large, which may cause system damage because of the resonance of the structure [4]. The arm needs to be redundant for better flexibility and adaptability, which tends to increase flexibility.…”
Section: Introductionmentioning
confidence: 99%